Exploring the impact of a student-centred survival swimming programme for primary school students in Australia: the perceptions of parents, children and teachers. (August 2021) - Petrass, Lauren A.; Simpson, Kate; Blitvich, Jenny; Birch, Rhiannon; Matthews, Bernadette
Teaching basic swimming, water safety and rescue skills is recommended by the World Health Organization for all school-aged children. However, there is a lack of evidence on effective pedagogies to develop swimming competency and the success of swimming lessons as a drowning prevention intervention. This study used a self-report questionnaire and practical testing procedures to examine the effectiveness of a 10-week student-centred aquatic programme designed for children aged 10–12 years. The study also determined whether the non-traditional swimming programme was accepted by swim teachers, school teachers and principals, and parents from a range of schools from different geographical regions in Victoria, Australia. A total of 204 students were enrolled in the programme. The pre-programme results indicated a good level of swimming, water safety and aquatic knowledge, but low swimming ability. Swimming ability significantly improved from pre-programme to post-programme, with no significant post-programme ability differences between male and female children or for participants from different programmes. Qualitative feedback collected through questionnaires, interviews and/or focus groups from students ( n = 73) and parents ( n = 69), school teachers and principals ( n = 14), swim teachers and swim school managers ( n = 21) indicated strong support from principals and swim teachers for the student-centred pedagogy, and all stakeholders valued the focus on survival swimming competencies. This research highlights the importance of including stakeholders when designing and implementing aquatics programmes. The study has resulted in a well-founded, effective programme with tailored resources and instructional materials that are available for swim centres and schools that would enable schools globally to adopt and implement this programme.